2012
DOI: 10.1111/j.1365-3016.2012.01272.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Factors and Hypospadias Risks

Abstract: SUMMARY We examined whether hypospadias was associated with several aspects of the diet, including intake of animal products, intake of several nutrients and food groups related to a vegetarian diet and estrogen metabolism, and diet quality. The study included deliveries from 1997 to 2005 that were part of the National Birth Defects Prevention Study. Diet was assessed by food frequency questionnaire during maternal telephone interviews, and two diet quality indices were developed based on existing indices. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Some studies examined a priori diet quality indices in relation to the risk of birth defects,13 14 24 but not of CHDs. The studies that used the DQI-P and MDS reported associations between increasing diet quality and reduced risk for some birth defects (neural tube defects and orofacial clefts13), but not others (microtia and hypospadias) 14 24. The magnitude of the risk reduction for CHDs in this study (table 2) is approximately similar, if slightly weaker, to that observed for neural tube defects and orofacial clefts with similar dietary indices 13.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies examined a priori diet quality indices in relation to the risk of birth defects,13 14 24 but not of CHDs. The studies that used the DQI-P and MDS reported associations between increasing diet quality and reduced risk for some birth defects (neural tube defects and orofacial clefts13), but not others (microtia and hypospadias) 14 24. The magnitude of the risk reduction for CHDs in this study (table 2) is approximately similar, if slightly weaker, to that observed for neural tube defects and orofacial clefts with similar dietary indices 13.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary approaches have only recently been applied to birth defect risk, and scarce population-based data are available. Recently, investigators from the National Birth Defects Prevention Study (NBDPS) have reported reduced risk for some birth defects (neural tube defects and orofacial clefts)13 but not others (hypospadias)14 with better maternal diet quality, as estimated by the Mediterranean Diet Score (MDS) and the Diet Quality Index for Pregnancy (DQI-P). Here we expand this dietary pattern approach to major non-syndromic CHDs.…”
Section: Introductionmentioning
confidence: 99%
“…The associations observed for birth defects other than CHDs, anorectal atresia and hypospadias, were unexpected, and warrant further analysis and replication in other study populations. A recent study of nutrient intake and hypospadias in the NBDPS found no association with dietary intake of vitamin C, an antioxidant vitamin, but vitamin E was not investigated (Carmichael et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Various nutritional risk factors have been suggested for hypospadias, including vegetarian diet, iron supplements, nutrients related to estrogen metabolism, and low quality diet [41,[63][64][65]. Carmichael et al (2012) evaluated these factors, but evidence was not supportive of associations with moderate to severe hypospadias [65].…”
Section: Nutritional Factorsmentioning
confidence: 99%
“…Various nutritional risk factors have been suggested for hypospadias, including vegetarian diet, iron supplements, nutrients related to estrogen metabolism, and low quality diet [41,[63][64][65]. Carmichael et al (2012) evaluated these factors, but evidence was not supportive of associations with moderate to severe hypospadias [65]. In contrast, in another study from the same group, maternal intake of certain phytoestrogens, i.e., plant-derived substances with estrogenic properties, and total phytoestrogen intake was negatively associated with moderate to severe hypospadias risk [66].…”
Section: Nutritional Factorsmentioning
confidence: 99%